Development and application of a slot-blot assay using the damage sensing protein Atl1 to detect and quantify O6-Alkylated Guanine bases in DNA - Yaakub, Hanum; Howell, Anthony; Margison, Geoffrey P; Povey, Andrew C (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Humans are unavoidably exposed to numerous different mutagenic DNA alkylating agents (AAs), but their role in the initiation of cancers is uncertain, in part due to difficulties in assessing human exposure. To address this, we have developed a screening method that measures promutagenic O6-alkylguanines (O6-AlkGs) in DNA and applied it to human DNA samples. The method exploits the ability of the Schizosaccharomyces pombe alkyltransferase-like protein (Atl1) to recognise and bind to a wide range of O6-AlkGs in DNA. We established an Atl1-based slot-blot (ASB) assay and validated it using calf thymus DNA alkylated in vitro with a range of alkylating agents and both calf thymus and human placental DNA methylated in vitro with temozolomide (TMZ). ASB signals were directly proportional to the levels of O6-meG in these controls. Pre-treatment of DNA with the DNA repair protein O6-methylguanine–DNA methyltransferase (MGMT) reduced binding of Atl1, confirming its specificity. In addition, MCF 10A cells were treated with 500 μM TMZ and the extracted DNA, analysed using the ASB, was found to contain 1.34 fmoles O6 -meG/μg DNA. Of six human breast tumour DNA samples assessed, five had detectable O6-AlkG levels (mean ± SD 1.24 ± 0.25 O6-meG equivalents/μg DNA. This study shows the potential usefulness of the ASB assay to detect and quantify total O6-AlkGs in human DNA samples.